STUDI PENDAHULUAN REKAYASA REMATURASI IKAN NILA (Oreohcromis niloticus) DENGAN PENAMBAHAN TELUR BEBEK (Anas domesticus) DAN TAUGE (Flammulina velutipes) DALAM PAKAN KOMERSIL - Elrifadah; Marlida, Rini; Ranu Susastra, Pandu (Chlorophyl, 2024)
Spawning is a stage carried out to support the availability of tilapia seeds. After being spawned, the broodstock requires a process of maturation of the gonads again (rematuration). The rematuration stage is very important to pay attention to because it greatly influences the success of spawning as well as the quantity and quality of the larvae produced.  This preliminary study aims to find out and examine the use of duck eggs (Anas domesticus) and bean sprouts (Flammulina velutipes) in feed to improve the quality of rematuration in tilapia.  The method used in this preliminary study is an exploratory descriptive method.  The test fish used were female tilapia fish that were 11 months old, started to be spawned on June 5 2023 and were recorded as having been spawned 7 times with an average weight of 200 grams. Broodstock selection will be carried out after spawning is complete. This selection aims to ensure that the fish are in healthy condition and ready for rematuration.  The feed used was floating feed manufactured by CPP with 29% protein. Apart from using manufactured feed in this research, duck eggs were also added at 12% and bean sprouts at 25% of the feed weight per day.  Feeding is done twice a day, namely morning and evening with a FR of 5% of biomass.   The research results showed that the HSI value of tilapia showed development during the rematuration period, getting an HSI value of 2.53% and a GSI value of 3.15%